Clinical and Epidemiological Features of Psoriasis in Patients Visiting Lumbini Medical College - Mikrani, Jameel Akhtar; Shrestha, Arati (Journal of Lumbini Medical College, 2016)
Background: Psoriasis is a worldwide disease and varies in its clinical profile and epidemiology in different regions of the world. The disease is common and few epidemiological data are available in our country. Objective: The purpose of this study was to evaluate the epidemiologic and clinical features of Psoriasis in Lumbini Medical College. Methods: A retrospective investigation of a total of 240 patients visiting Out Patient Department (OPD) of Dermatology and Venereology of Lumbini Medical College with Psoriasis was done. The parameters included were age at onset of disease, age at first treatment, current age, sex, type of disease and distribution of lesions. Data and statistical analysis was done with SPSS 17.0. Results: The mean age of patients at onset of disease was 26.4 (SD = 14.3) years. M:F ratio was 1.16. Psoriasis vulgaris (PV) was the most common variety of the disease. Extensor surface of the body was most commonly involved. Conclusion: Psoriasis is a common dermatological disease accounting 2.9% of all dermatology patients in our center. PV is the most common clinical subtype. The disease is more frequent in the third decade of life and has a male predominance in our region. Treatment compliance has been found to be poor. Journal of Lumbini Medical College. 2014;2(1):1-3.